Tracking red blood cells flowing through a microchannel with a hyperbolic contraction: an automatic method - Taboada, Bruna Rafaela Pereira (2018)
The present chapter aims to assess the motion and deformation index of red blood cells (RBCs) flowing through a microchannel with a hyperbolic contraction using an image analysis based method. For this purpose, a microchannel containing a hyperbolic contraction was fabricated in polydimethylsiloxane by using a soft-lithography technique and the images were captured by a standard high-speed microscopy system. An automatic image processing and analyzing method has been developed in a MATLAB environment, not only to track both healthy and exposed RBCs motion but also to measure the deformation index along the microchannel. The keyhole model has proved to be a promising technique to track automatically healthy and exposed RBCs flowing in this kind of microchannels.